Ceiling-fan-integrated air-conditioning: thermal comfort evaluations. Issue 1 (23rd December 2021) - Luo, Maohui; Zhang, Hui; Wang, Zi; Arens, Edward; Chen, Wenhua; Bauman, Fred S.; Raftery, Paul
Ceiling-fan-integrated air-conditioning (CFIAC) is a concept in which terminal supply ducts and diffusers are replaced by vents/nozzles that jet supply air into the vicinity of ceiling fans to be mixed and distributed within the room. CFIAC distributes the supply air within the room and convectively cools the occupants. This could allow raised thermostat set-points and reduced energy for the air-conditioning system's supply fan and compressor. Previous work on CFIAC shows that the air temperature in the occupied zone is spatially uniform, but the air speed is not. This paper evaluates the thermal comfort performance of a CFIAC system under various ambient temperatures and fan operation modes. Human subject experiments and thermal manikin tests were conducted to characterize how subjects evaluate the thermal comfort performance across the room's floorplate, and how CFIAC affects human body heat transfer. Despite the spatial variation in air speed across the floorplate, CFIAC created uniform thermal comfort perceptions. Comfort at 28°C was similar to that of 26°C for the overhead supply neutral reference condition. Human subjects preferred having the increased air movement over that of the reference condition. The paper evaluates thermal comfort indexes appropriate for evaluating and designing CFIAC. Practice relevance: Despite the spatial variation in air speed across the floorplate, CFIAC created quite uniform thermal comfort perceptions. Conventional air-conditioning systems often create overcooling complaints because supply volumes through diffusers are kept overly high in order to disperse cold temperature dumping in the space. Ceiling fan circulation provides sufficient dispersion to eliminate this issue. However, it is important for standards writers and designers to understand that the room temperatures should not be so cold that the highest airspeeds caused by the ceiling fans will be uncomfortable for the occupants in the fan-cooling zone. To evaluate CFIAC systems, the standard effective temperature (SET) model is shown to be useful and the elevated air speed method in American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) Standard 55 also provides appropriate design guidance.